2019
DOI: 10.1097/md.0000000000017106
|View full text |Cite
|
Sign up to set email alerts
|

Associations between miR-146a rs2910164 polymorphisms and risk of ischemic cardio-cerebrovascular diseases

Abstract: Background:Many studies investigated the association between miR-146a rs2910164 polymorphisms and risk of ischemic cardio-cerebrovascular diseases. However, the results were inconsistent.Methods:We searched the PubMed, EMBASE, Cochrane library, Web of Science, Chinese National Knowledge Infrastructure, VIP, and Wanfang databases for appropriate studies. Odds ratios (ORs) with 95% confidence intervals (CIs) were calculated to evaluate the associations. Heterogeneity, sensitivity, and publication bias were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
2
1
Order By: Relevance
“…It has been reported that miR-146a levels were shown to be greater in AMI patients of the Chinese population, and the GG phenotype of MIR146A rs2910164 was linked with a higher risk of AMI than the CC phenotype [ 49 ]. In contrast to our findings, a previous study found that the MIR146A rs2910164 variant is associated with a reduced risk of CHD in the Asian population [ 50 ]. A recent study by Mehrjardi et al revealed no statistically significant correlation between the MIR146A gene polymorphism (rs2910164) and CAD within the Iranian population [ 51 ].…”
Section: Discussioncontrasting
confidence: 99%
“…It has been reported that miR-146a levels were shown to be greater in AMI patients of the Chinese population, and the GG phenotype of MIR146A rs2910164 was linked with a higher risk of AMI than the CC phenotype [ 49 ]. In contrast to our findings, a previous study found that the MIR146A rs2910164 variant is associated with a reduced risk of CHD in the Asian population [ 50 ]. A recent study by Mehrjardi et al revealed no statistically significant correlation between the MIR146A gene polymorphism (rs2910164) and CAD within the Iranian population [ 51 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Cerebrovascular disease refers to acute and chronic cerebrovascular diseases caused by various reasons. As a common and frequently occurring disease in the nervous system, cerebrovascular disease is currently one of the three major diseases leading to human death, second only to cardiovascular disease and cancer ( 1 , 2 ). Ischemic cerebrovascular diseases mainly include transient ischemic attack and cerebral infarction, accounting for about 80% of all strokes, and the proportion is higher in elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 , 11 ] Studies show that miR-146a is involved in the process of CHD. [ 12 , 13 ] For instance, a previous study showed that miR-146a expression was higher in the coronary artery disease (CAD) group. [ 14 ] Furthermore, treatments with angiotensin II receptor blockers and statin could suppress the level of miR-146a and toll-like receptor 4 signal pathway, which might be the molecular mechanism concerning the anti-atherosclerosis of angiotensin II receptor blockers and statin in CAD patients.…”
Section: Introductionmentioning
confidence: 99%